2002
DOI: 10.1002/1521-3757(20020517)114:10<1808::aid-ange1808>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Pentaphosphaferrocen als verknüpfende Einheit in ein- und zweidimensionalen Polymeren

Abstract: Professor Joachim Str‰hle zum 65. Geburtstag gewidmetF¸r den Aufbau diskreter supramolekularer [1] Aggregate, Netzwerke und Koordinationspolymere [2] durch Selbstorganisation werden¸blicherweise N-Heterocyclen als N-Donorliganden verwendet, um verschiedene Metallzentren miteinander zu verkn¸pfen. Im Unterschied dazu besteht unser Ziel auf diesem Gebiet in der Nutzung von P n -Ligandkomplexen als verkn¸pfende Einheiten zwischen Metallkationen, um wohlorientierte Aggregate oder eindimensionale (1D) und zweidim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 39 publications
1
14
0
9
Order By: Relevance
“…[1] Contrary to familiar methods in this field which make use of N-and O-donor-containing ligands, respectively, for connecting different metal centers, our strategy until now has been focused on the use of P nligand complexes as connecting moieties. We have already shown that the tetrahedrane complex [{CpMo(CO) 2 } 2 (m,h 2 -P 2 )] can be used as an efficient building block for the formation of oligomers and polymers [2,3] in the presence of Cu I and Ag I salts and that the pentaphosphaferrocene complexes [Cp x Fe(h 5 -P 5 )] (Cp x = C 5 Me 5 (Cp*), C 5 Me 4 Et) form 1D and 2D polymers [4] as well as spherical fullerene-like aggregates [5,6] upon reaction with Cu I halides. The Florentine groups of Stoppioni and Peruzzini were able to show that [(triphos)M(h 3 -P 3 )] (M = Co, Rh, or Ir; triphos = 1,1,1-tris-(diphenylphosphanylmethyl)ethane) coordinates with Cu I , Ag I , or Au I centers to form monocationic complexes.…”
Section: Dedicated To Professor Hansgeorg Schnöckel On the Occasion Omentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Contrary to familiar methods in this field which make use of N-and O-donor-containing ligands, respectively, for connecting different metal centers, our strategy until now has been focused on the use of P nligand complexes as connecting moieties. We have already shown that the tetrahedrane complex [{CpMo(CO) 2 } 2 (m,h 2 -P 2 )] can be used as an efficient building block for the formation of oligomers and polymers [2,3] in the presence of Cu I and Ag I salts and that the pentaphosphaferrocene complexes [Cp x Fe(h 5 -P 5 )] (Cp x = C 5 Me 5 (Cp*), C 5 Me 4 Et) form 1D and 2D polymers [4] as well as spherical fullerene-like aggregates [5,6] upon reaction with Cu I halides. The Florentine groups of Stoppioni and Peruzzini were able to show that [(triphos)M(h 3 -P 3 )] (M = Co, Rh, or Ir; triphos = 1,1,1-tris-(diphenylphosphanylmethyl)ethane) coordinates with Cu I , Ag I , or Au I centers to form monocationic complexes.…”
Section: Dedicated To Professor Hansgeorg Schnöckel On the Occasion Omentioning
confidence: 99%
“…Structure of the dication of 5 in the crystal; hydrogen atoms omitted for clarity. Selected bond lengths [] and angles[8]: As1-As2 2.452(2), As1-As3 2.368(2), As2-As3 2.464(2), As4-As5 2.528(2), As4-As6 2.371(2), As5-As6 2.369(2), Ag1-As1 2.828(1), Ag1-As2 2.806(1), Ag1-As2' 2.823(1), Ag1-As3' 2.780(1), Ag1-As4 2.704(2), Ag1-As5 2.665(1); As1-Ag1-As2 51.59(4), As1-Ag1-As2' 105.02(4), As1-Ag1-As3' 82.26(4), As1-Ag1-As4 96.65(4), As1-Ag1-As5 151.49(5), As2-Ag1-As2' 90.09(4), As2'-Ag1-As3' 52.16(4), As2-Ag1-As3' 111.33(4), As2-Ag1-As4 101.54(4), As2'-Ag1-As4 158.17(5), As2-Ag1-As5 135.13(5), As2'-Ag1-As5 102.72(4), As3'-Ag1-As4 135.69(5), As3'-Ag1-As5 110.35(5), As4-Ag1-As5 56.17(4). Proposed equilibrium of the monocation I and dication II (DFT-calculated structures) in CH 2 Cl 2 at room temperature.…”
mentioning
confidence: 99%
“…Das ähnlichste Polyphosphorderivat ist Pentaphosphaferrocen [Cp*Fe(h 5 -P 5 )] (Cp* = h 5 -C 5 Me 5 ) (1). [7] Wir und die Gruppe um Scherer sind an der Reaktivität von 1 interessiert, und es konnte gezeigt werden, dass die cylco-P 5 -Einheit an Übergangsmetallcarbonyle koordinieren kann, wobei Tripeldecker-Komplexe und andere metallorganische Verbindungen mit verzerrten P 5 -Einheiten gebildet werden, [8] und an Kupfer(I)-Halogenide, was zur Entstehung von 1D-und 2D-Polymeren [9] oder sogar sphärischen Fulleren-artigen Superbällen führt. [10] Die Redoxchemie von 1 wurde zunächst durch Winter und Geiger untersucht.…”
unclassified
“…¾hnlichkeiten wurden bei der Bildung von Tripeldeckerkomplexen [6,7] oder bei Cp/cyclo-P 5 -Übertragungsreaktionen beobachtet, [8] während Fragmentierungen und Verzerrungen des cyclo-P 5 -Ringes von 1 als wesentlichste Unterschiede zwischen beiden Verbindungen gefunden wurden. [9,10] Zusätzlich erçffnet die Existenz freier Elektronenpaare an den Phosphoratomen eine extensive Koordinationschemie der cyclo-P 5 -Einheit, die zu 1D-und 2D-Polymeren [11] sowie zu sphärischen Fullerenartigen Supramolekülen führt. [12] Ein Blick auf die HOMO-und LUMO-Orbitals des Ferrocens zeigt die eisenzentrierte Reaktivität des Ferrocens während der Oxidation und Reduktion.…”
unclassified